Poligami Vis a Vis Monogami (Analisis Dalil Normatif dan Sosio-Historis Legalitas Poligami dalam Literatur Keislaman) - Fudola, Intihaul; Yusuf, Wildan Fatoni (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2024)
Abstract The issue of polygamy has always been a social problem that causes polarization between the groups that support and reject it. This discussion should no longer revolve around whether polygamy is allowed. Furthermore, the discussion on polygamy should lead to the issue of how polygamy can be placed proportionally as something logical and just. This article seeks to situate the issue of polygamy by reviewing various perspectives. The focus of this study is as follows. 1) What is the background to the legality of polygamy in Islam? 2) Does Islam advocate polygamy or monogamy, the model of marriage expected by Islam? This study used a library research method. The approaches used were the normative approach (fiqh), the social conditions of society when the polygamy verse was revealed (socio-historical), and the cultural approach of pre-Islamic society. The results show that 1) polygamy was legalized at that time because it aimed to avoid the Arab habit of marrying female orphans and engaging in injustice. Instead, Islam legalized the polygamy that had become a tradition of the Arabs before as an emergency measure. 2) Islam came to reduce the practice of polygamy, which was done far from justice. Instead, monogamy became the principle of marriage expected by Islam to achieve the goal of marriage: sakinah, mawaddah, and rahmah. Keywords: Polygamy, Monogamy, Islam